A Medical Student Qualitative Study of Rural Health Concerns, Community Determinants and Whole Person Care - Harper, Andrew; Sanders, Kiera; Edwards, Kahla; Billah, Tasfeen; Corbett, Tessa; Irvine, Lucy (The International Journal of Whole Person Care, 2024)
Background: Following a short rural health placement in the second year of medical school five students opted, as an extra-curricular activity, to conduct an exploratory research project into the wellbeing and health concerns of rural residents in the Wheatbelt of Western Australia. The project was conducted in collaboration with the local shires. The aim was to document, analyse and understand the health concerns and experience of rural residents.Methods: A phenomenological research approach was employed. Seventeen rural residents selected by the shires, and four key informants responded to open-ended interviews. Their narratives were subjected to a thematic analysis.Results: The narratives described a wide range of health concerns relating to health services, mental illness, transportation, accommodation, marginalisation of the community, bureaucratisation of administration, community fragmentation and the desire for community partnerships. Frustration and inconvenience from community factors were associated with anxiety, depression, isolation, and loss of wellbeing.Discussion: The respondents described dysfunctional infrastructure and under resourcing in a local rural community. They defined numerous health concerns related to deficiencies in community cohesion and integration. They illustrated how whole person health is impacted by the infrastructure and services available within a rural community. The narratives highlight the need for adaptation at the community level, following the example of Health in All Policies. Participants also highlighted the need for clinicians trained in supporting the functioning of the whole person within a fragmented rural environment.